Bedside teaching: An indispensable model of patient‑centred teaching in undergraduate medical education - Asani, Mustafa (Nigerian Journal of Basic and Clinical Sciences, 2026)
Bedside teaching remains the most effective way of imparting competency in clinical skills in undergraduate medical education but there has been a noticeable decline in the practice of bedside teaching worldwide. This paper aims to emphasise the importance of bedside teaching, highlights the possible barriers to effective bedside teaching and equip medical teachers with the effective ways of achieving the intended goals of bedside teaching by emphasising the techniques recommended by experts in the field of medical education. Developed countries have employed the use of clinical skill centres to cushion the effect of the decline in bedside teaching, but in resource-limited countries it remains the only viable option. The advantages of bedside teaching include; learning in context, impartation of clinical skills, nurturing and development of clinical reasoning. In addition, bedside teaching provides opportunity for role modelling, professional thinking, observation of communication skills, team work and integration of communication skills, clinical skills and ethical issues in the process of patient care. Several hindrances to effective bedside teaching have been identified. These include a large student: teacher ratio, crowded lectures, improper use of logbooks, lack of preparedness and interest, increasing administrative and research works among medical teachers. The strategies recommended by experts can be categorised into three; based on the timing as; before, during and after bedside teaching. These emphasise the need for adequate preparation, setting of clear objectives before teaching, active participation, gentle correction during teaching, feedback and discussion of sensitive issues away from the patient.
Keywords: Bedside teaching; teachers; undergraduate